Beispiel Nr: 24
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 3x +5y =8\\ 9x +0y = 7 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 3 x +5 y =8\\ II \qquad 9 x +0 y = 7 \\ \text{I nach x auflösen}\\ 3 x +5 y =8 \\ 3 x +5 y =8 \qquad /-5 y\\ 3 x =8 -5 y \qquad /:3 \\ x =2\frac{2}{3} -1\frac{2}{3} y \\ \text{I in II}\\ 9 (2\frac{2}{3} -1\frac{2}{3} y ) + 0 y = 7 \\ 24 -15 y +0 y = 7 \qquad / -24 \\ -15 y +0 y = 7 -24 \\ -15 y = -17 \qquad /:\left(-15\right) \\ y = \frac{-17}{-15} \\ y=1\frac{2}{15} \\ x =2\frac{2}{3} -1\frac{2}{3} y \\ x =2\frac{2}{3} -1\frac{2}{3} \cdot 1\frac{2}{15} \\ x=\frac{7}{9} \\ L=\{\frac{7}{9}/1\frac{2}{15}\} \end{array} & \begin{array}{l} I \qquad 3 x +5 y =8\\ II \qquad 9 x +0 y = 7 \\ \text{I nach y auflösen}\\ 3 x +5 y =8 \\ 3 x +5 y =8 \qquad /-3 x\\ 5 y =8 -3x \qquad /:5 \\ y =1\frac{3}{5} -\frac{3}{5}x \\ \text{I in II}\\ 9x + 0(1\frac{3}{5} -\frac{3}{5} x ) = 7 \\ 0 -0 x +0 x = 7 \qquad / -0 \\ -0 x +0 x = 7 -0 \\ 9 x = 7 \qquad /:9 \\ x = \frac{7}{9} \\ x=\frac{7}{9} \\ y =1\frac{3}{5} -\frac{3}{5} x \\ y =1\frac{3}{5} -\frac{3}{5} \cdot \frac{7}{9} \\ y=1\frac{2}{15} \\ L=\{\frac{7}{9}/1\frac{2}{15}\} \end{array} \end{array} $